THE RELATIONSHIP BETWEEN TEACHER INTERPERSONAL BEHAVIOR AND STUDENT ATTITUDE TOWARD SCIENCE LEARNING IN PRIMARY SCHOOL: INDONESIAN CASE STUDY - Mustafa Kamal Nasution (Jurnal Visipena, 2012)
This study proposes to assess the relationship between student perceptions on teacher interpersonal behavior and student attitude toward Science in Indonesian Primary school. This research engaged 143 students from SDN 47 Jambi, Indonesia. To gather the data, two types of questionnaires were used; Test of Science Related Attitude (TOSRA) and the Indonesian version of the Questionnaire Teacher Interpersonal (QTI). SPSS program were applied to process the data statistically. The result shows that the questionnaires are relatively reliable for Indonesian primary students. Acceptability of Cronbach alpha coefficient was found in both actual and preferred situation. The findings also reveal that from the students’ view, their teachers have relatively good Leadership and Understanding in the classroom, less Uncertainty, Dissatisfaction and Admonishment toward students. However, the students perceive to some extent unfavorable perceptions on their Freedom and teacher Strictness. Another analysis describes that there are significant differences between actual and ideal perceptions on the whole scale of QTI except on Uncertainty. Furthermore, between male and female perceptions, this study finds that there are significant differences on Helping, and Strictness. Lastly, the multiple correlation analysis explaines that there is a correlation between the scale of QTI and Enjoyment toward science, in which Uncertainty and Admonishment scales are significantly negative affect students’ enjoyment in science classroom.